Semiotic Analysis of "Hyundai Presents Re:Style 2020" Green Marketing in Automotive Ads - An'Umillah, Sayyidatu Ahya; Sudrajat, Ratih Hasanah (ARISTO, 2024)
One detrimental consequence of the automotive industry's excessive production is the accumulation of end-of-life vehicles (ELV). ELV ought to be disposed of via a waste recycling system. As a result, the automotive sector bears a substantial obligation with regard to ELV. Hyundai is one of the automotive industries that has managed ELV effectively. The YouTube advertisement for the Hyundai Re:Style Presents 2020 model illustrates this. Hyundai's collaboration with fashion designers to recycle automobile byproducts including leather, airbags, seat belts, and glass is featured in the advertisement. They create fashion items from waste, including jewelry, denim jumpsuits, work vests, corsets, and tote bags. Researchers are intrigued by the pursuit of investigating the significance of the sign representation, the object, and the interpretant, as well as the implications of advertising within the framework of green marketing theory. To achieve this aim, the semiotic theory of Charles Sanders Peirce was employed by featuring a triadic model comprising an object, representation, and interpretant. Additionally, Sinh's green marketing framework was incorporated, comprising a green place, green product, green price, and green promotion. Consequently, A qualitative research based on Charles Sanders Peirce's semiotics was used. The results shows that the signs, objects, and interpretants in Hyundai advertisements show the meaning of green marketing.